Macro-SAMs for modelling purposes: an application to Portugal in 2003 - Santos, Susana (2009)
Knowledge of the quantifiable side of a market economy greatly depends on the form of macro-economic modelling that is used. This, in turn, should have an underlying database. Such a database should include the interrelated subsystems that exist within that economy and, at the same time, it should be adaptable for modelling purposes, whilst also being flexible and consistent, in order to allow for aggregations and disaggregations. Based on the geographical limits of a European country and the time limit of one year (1 January to 31 December), this paper proposes, as a possible database, a Social Accounting Matrix (SAM) constructed from the national accounts, operating within the framework of the European System of National and Regional Accounts in the European Community of 1995 (ESA 95). Using a numerical version of a SAM, constructed from the Portuguese national accounts for 2003, at a highly aggregated level, the aim of this paper is to show the differences between a matrix format of the national accounts, as proposed by the ESA 95 and the United Nations System of National Accounts for 1993 (SNA 93), from which it is constructed, and the SAM, emphasizing its potentialities as a database for modelling purposes. Some considerations will also be made about the relationship between SAMs and Input-Output tables.